Avaliação do pavimento flexível e cálculo do reforço pelos métodos DNER-PRO 11/79 e 269/94 - Azoia, Wesley Gimenes (2014)
The asphalt paving is an integral part of the infrastructure of a country, state and county party because it brings security and comfort to users and facilitates mobility. Like any building, the floor also needs periodic maintenance to continue ensuring a quality usefulness. When there is impairment of the pathway, you must provide evaluations followed by reinforcement projects applying superficial fixes and increased structural capacity to support new traffic requests. This work aims to evaluate the pavement of Nelson Maior Avenue in the City of Terra Rica - Paraná and after diagnosis of the current situation, perform scaling methods by 11/79 and 269/94 to safely recover their properties and propose a solution resurfacing in two stretches of the boulevard. Assays for soil characterization were performed at the Laboratory of the Federal Technological University of Paraná, Campo Mourão campus. Followed their specific standards. The scaling method 11/79 and its procedures and calculations were governed by "DNER-PRO 11/79 - Structural Evaluation of Flexible Pavements" and the standard method 269/94 followed the "DNER-PRO 269/94 rule - Draft restoration of Flexible Pavements ", besides the determination of drainage in the sections with the location of inlets. After evaluations, the diagnosis of the payment found that the two sites presented surface defects that impair the safety of users, however the structural support is in good quality because of low deflection and radius of curvature high, not compromising the lower layers: base , subbase and subgrade. The two scaling methods and obtained similar results reinforce the need to only superficial intervention, noting that the existing layer supports current and future traffic. A proposed remedial measure .The proposed remedial measures in hot asphalt concrete (HMA) of three inches thick allows the surface layer to be recovered and recomposed making the floor safe and feasible for users. Those performed by the respective technical standards reviews ensure a diagnosis with quality by the amount of information provided, as well as scaling by different methods ensure greater confidence on the part of the designers for making quality designs and confirm the prudence of a feasible restoration servicing requests gifts no brief maintenance.